SEKOLAH RAMAH ANAK SEBAGAI WUJUD PERLINDUNGAN TERHADAP HAK ANAK DI SEKOLAH DASAR - Chairiyah, Chairiyah; Nadziroh, Nadziroh; Pratomo, Wachid (TRIHAYU: Jurnal Pendidikan Ke-SD-an, 2021)
A school is a place for the government to carry out its obligations to fulfill the education rights of Indonesian citizens. In addition to the right to education which is a constitutional mandate, schools are also part of the fulfillment of children's rights based on Law Number 39 of 1999 concerning Human Rights and Law Number 23 of 2002 concerning Child Protection. The formulation of the Child-Friendly School program involved 12 ministries, agencies, and foundations related to child welfare. The goal of the Child-Friendly School policy is to be able to fulfill, guarantee and protect the rights of children. Another goal is to ensure that schools can develop children's interests, talents, and abilities and prepare children to be responsible for a life of tolerance, mutual respect, work together for progress, and a spirit of peace so that later schools are expected to not only give birth to an intellectually intelligent generation but also give birth to an emotionally and spiritually intelligent generation.Ã‚Â